Manganese dioxide/cobalt tungstate/ nitrogen-doped carbon nano-onions nanocomposite as new supercapacitor electrode. Issue 1 (1st January 2022) - Sohouli, Esmail; Adib, Kourosh; Maddah, Bozorgmehr; Najafi, Mostafa
Abstract: Application of the electrochemical supercapacitors is one way to store energy, which has widely attracted scientists worldwide. In this regard, in the present work, a triple-segment nanocomposite of manganese dioxide, cobalt tungstate, and nitrogen-doped carbon nano onions ( MnO2 /CoWO4 /NCNO) was prepared based on a facile chemical method. The synthesized nanomaterials were analyzed by X-ray diffraction, infrared, as well as scanning electron microscopy. The supercapacitive properties of the synthesized nanomaterials were checked using electrochemical impedance spectroscopy, galvanostatic charge-discharge and voltammetry methods. The value of specific capacitor for the prepared electrodes containing MnO2, CoWO4, NCNO, MnO2 /CoWO4, and MnO2 /CoWO4 /NCNO in an alkaline electrolyte (KOH: 6 M) at a current density of 2 A/g have obtained as 209, 97, 170, 413, and 536 F/g, respectively (Three-electrode system). Also, the retained stability of the MnO2 /CoWO4 /NCNO electrode after 3000 consecutive charges and discharges was 96%. The supercapacitive behavior and excellent capacitance of the MnO2 /CoWO4 /NCNO electrode was due to the synergistic effects of MnO2, CoWO4, and NCNO. A two-electrode symmetric supercapacitor assembled device is fabricated and exhibits a high specific capacitance of 1036 F/g at 2 A/g. It shows that the MnO2 /CoWO4 /NCNO composite provides potential applications in energy storage. Graphical abstract: Image 1